Fenomena Healing dan Self-Love di Media Sosial Instagram: Tinjauan Psikologis pada Tren Budaya Populer - Nila Vinca Risma Trisna (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the phenomenon of healing and self-love on Instagram as psychological expressions within digital popular culture. The research is grounded in the rising use of mental health-related hashtags such as #healing and #selflove, which have been used over 51 million and 130 million times respectively in 2025. Using a qualitative approach with content analysis, the study examines public Instagram posts containing these hashtags. A thematic content analysis was conducted to identify the psychological meanings and cultural representations embedded in the content. The findings indicate that healing and self-love trends reflect a paradigm shift from clinical approaches toward more open social expressions of well-being. Drawing on Kristin Neff’s Self-Compassion theory and Martin Seligman’s Positive Psychology, these trends embody values of mindfulness, self-kindness, and resilience that contribute to users’ psychological well-being. However, the phenomenon also shows ambivalence, as it often turns into consumptive and performative behavior. Therefore, balance between self-reflection and social responsibility is needed to maintain authentic healing practices.